2020
DOI: 10.3390/agronomy10020232
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Yield, Fiber Quality and Dry Matter Production of Cotton Planted at Various Densities under Equidistant Row Arrangement

Abstract: The number of cotton plants grown per unit area has recently gained attention due to technology expense, high input, and seed cost. Yield consistency across a series of plant populations is an attractive cost-saving option. Field experiments were conducted to compare biomass accumulation, fiber quality, leaf area index, yield and yield components of cotton planted at various densities (D1, 1.5; D2, 3.3; D3, 5.1; D4, 6.9; D5, 8.7; and D6, 10.5 plants m−2). High planting density (D5) produced 21% and 28% more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In this study, higher densities showed higher aboveground biomass and yield in population, which may be because a higher density of plants with greater light interception presents a higher speed and longer period of fast biomass accumulation, for single plant the D1 density of plant was significantly higher than others, the reason was that the plants in low densities have less competition which each other, and each plant can receive enough light interception for growth, but the whole plant population was less competitive than the high-density ones. The trend of aboveground biomass accumulation followed the same rules as in Khan's study [30], and the aboveground biomass of a single plant and the whole population growing at different densities were both linearly related to cumulative iPAR [14,41]. However, low plant densities present lower cotton productivity, that may be because early leaf senescence may cause low light-use efficiency in a population, which furthermore reduces boll weight [50].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In this study, higher densities showed higher aboveground biomass and yield in population, which may be because a higher density of plants with greater light interception presents a higher speed and longer period of fast biomass accumulation, for single plant the D1 density of plant was significantly higher than others, the reason was that the plants in low densities have less competition which each other, and each plant can receive enough light interception for growth, but the whole plant population was less competitive than the high-density ones. The trend of aboveground biomass accumulation followed the same rules as in Khan's study [30], and the aboveground biomass of a single plant and the whole population growing at different densities were both linearly related to cumulative iPAR [14,41]. However, low plant densities present lower cotton productivity, that may be because early leaf senescence may cause low light-use efficiency in a population, which furthermore reduces boll weight [50].…”
Section: Discussionmentioning
confidence: 53%
“…The samples were then dried at 80 • C for 48 h until a constant weight was achieved. A logistic regression formula was used to calculate biomass accumulation [30]:…”
Section: Biomassmentioning
confidence: 99%
“…The shedding of boll was mainly concentrated in the outer fruit nodes of the middle and lower fruiting branches, and the boll shedding rate increased with increasing density. Because the high-density canopy was relatively closed, especially in the middle and lower sections, the light transmission is less [42], and then the temperature decreases and the relative humidity increases [43], resulting in an increase in boll shedding. Li thought that the closer squares and bolls are to the main stem, the fewer fall off, and the greater bolls formed [44].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were taken every 15 days from the seeding stage at 30, 45, 59, 73, 88, 99, 115, 128, and 145 DAE in 2019 and at 28,43,58,73,87,98,113, and 128 DAE in 2020, with three repeats each time. Two representative plants with the same growth were selected in each plot, and the parts above the cotyledon nodes were separated according to leaves, stems, and reproductive organs (squares, flowers, bolls, catkins).…”
Section: Leaf Area and Biomassmentioning
confidence: 99%
“…The proper planning density for any crop can vary considerably depending on many agronomic factors such as sowing time, fertilization, soil moisture and pest management for different geographic locations. Accordingly, Khan et al [3] find that the adoption of a planting density of 8.7 plants m −2 enhances cotton yield and fiber quality, as compared to the conventional wider rows and lower plants ha −1 adopted in the studied area. Through further field trials, Khan et al [4] examine over two growing seasons the effects of three planting densities (low, 3 × 10 4 ; medium, 6 × 10 4 ; high, 9 × 10 4 plant ha −1 ) on lint yield, leaf structure, chlorophyll fluorescence and leaf gas exchange attributes in two cotton cultivars ('Zhongmian-16 and 'J-4B').…”
mentioning
confidence: 82%